Effectiveness of progressive core stabilization training on anaerobic performance in elite athletes: a randomized controlled trial - Basandaç, G.; Bargi, G.; Tunay, V. B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Although progressive core stabilization training (PCST) improves sport-specific abilities, the effects of PCST on anaerobic performance and fatigue are still unclear today. Therefore, this prospective, single-blind (blinded: athletes, using placebo intervention), randomized (using random selection method) controlled study aimed to investigate the presence of these effects in elite athletes.